Corneal Endothelial Morphology in Children with Type 1 Diabetes - Mohamed Anbar; Hatem Ammar; Ramadan A. Mahmoud (Journal of Diabetes Research)
Aim. To investigate corneal endothelial cell morphological in children with type 1 diabetes and to determine the systemic and local factors that contribute to these changes. Methods. One hundred sixty eyes of 80 children with type 1 diabetes and 80 eyes of 40 normal children as a control during the period from July 2015 to February 2016 underwent full clinical and ophthalmologic examination. We measured the central corneal thickness (CCT), endothelial cell density (ECD), ploymegathism, and pleomorphism using a noncontact specular microscope. Results. The mean age of the diabetic children was 8.22±3.11 years. The mean duration of type 1 diabetes was 3.51±2.23 years. The mean CCT was significantly higher: 537±33.41 microns (right eye), in the diabetic group compared to the control group. The mean ECD in patients with type 1 diabetes was 3149.84±343.75 cells/mm2 (right eye), and it was significantly lower than in the control group. Furthermore, pleomorphism was significantly lower 48.73±5.43% (right eye), in the diabetic group compared to the control group. The mean polymegathism was significantly higher 37.96±5.61% (right eye), in the diabetic group compared to the control group. All of these changes are significantly correlated only with the duration of diabetes. Conclusions. Diabetic children have thicker corneas, lower ECD, an increased polymegathism, and a decreased pleomorphism. The duration of diabetes is the factor that affects all of these changes. To what extent these changes affect visional function on long term needs to be investigated in further studies.